Halal entrepreneurship from Maqasid-al-Sharia’h perspective: an inseparable concept for Halalpreneurs - Abdullah, Moha Asri; Azam, Siddique (Rynnye Lyan Resources, 2020)
Entrepreneurship has become one of the vital activities for economic development. It is synonymous with job creation, innovation, improvement in the societal well-being and economic growth in developed and developing countries alike. There is a great interest in entrepreneurship globally as well as in Malaysia. Over the past few years, many individuals, as well as families, are actively engaged with the small business. Also, in light of the 2013 GEM study, 12.7% of Americans are effectively occupied with beginning a business or are the proprietor/director of a business that is under three years of age. Simultaneously, the Halal industry, which represents the global Islamic economy, is the fastest-growing market in the world with a $2.3 trillion market value. Halal entrepreneurs (Halalpreneurs) are the major contributors to this achievement as they constitute a significant portion of the total establishment in most of the Muslim countries. That is the reason Entrepreneurship has turned into a conventional term that depicts a wide range of practices that include being innovative, devilish and tricky. Entrepreneurship has been defined by many scholars, researchers, industry players, and academicians globally which have also been perceived in the same way by most of the economies around the world. However, the Islamic economy looks at the concept of ‘entrepreneurship’ in a different way and perceives it as ‘Halalpreneurship’. To define entrepreneurship in the halal industry, although, the term ‘Halalpreneurship’ is being used, surprisingly the term has not been defined properly yet. It is essential for the Muslim entrepreneurs to have a proper understanding of Halalpreneurship from Maqasid-al-Shariah perspective. Such a point of view is crucial to justify the term in the Halal industry and differentiate from conventional entrepreneurs. In this context, this paper provides a concept and definition of Halalpreneurship justifying from the perspective of Maqasid-al-Sharia’h. It also identifies the differences between Halalpreneurs and entrepreneurs using secondary resources available in the forms of literature, research papers, journal papers, articles, conference papers, online publications, etc. The findings of the study will clarify the concept of Halalpreneurship from Maqasid-al-Sharia’h perspective and recognize Halalpreneurs distinguished from conventional entrepreneurs.